PERAN MEDIA SOSIAL, INFLUENCER, DAN ASSURANCE AWARENESS TERHADAP KEPUTUSAN PEMBELIAN ASURANSI JIWA BAGI GENERASI Z - Yerizal, Yerizal; Septaria, Vera; Sovia, Arina (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2025)
In Indonesia, there are around 21.94 million individuals, or only 8 percent of the total population who have life insurance as a protection effort in family financial planning. In the context of family financial needs that continue to grow along with various stages of life, the existence of life and financial protection is very important, especially for customers who are at productive age, especially young families. This study aims to analyse the influence of social media, influencers on life insurance awareness and the decision to buy life insurance products among Generation Z. This research is quantitative research and the sampling technique is purposive sampling, with data collected from 150 respondents through questionnaires. Data analysis was conducted using Smart PLS 4.0. The results showed that the positive influence of influencers significantly increased life insurance awareness (β = 0.45; p < 0.01), which in turn contributed to the decision to purchase life insurance (β = 0.35; p < 0.01). In addition, social media serves as a mediator that strengthens the relationship between influencer influence and purchase decision (β = 0.25; p < 0.01). These findings indicate that Generation Z values authenticity and emotional connection more than just influencer popularity, so insurance companies should choose relatable influencers to effectively reach this audience.The originality of this research is to highlight how awareness of life insurance serves as a bridge that connects social media and influencers to Gen Z's decision to buy life insurance. Then focusing on Generation Z, this research provides new insights into how information delivered through digital platforms can shape their understanding and attitudes towards life insurance products.The managerial implications of this study emphasise the importance of a more personalised and value-based marketing strategy in promoting insurance products. Insurance companies are advised to actively utilise social media platforms, establish strong relationships with influencers, and provide informative and engaging content for Generation Z. With this approach, it is expected that awareness and life insurance decisions among Generation Z can increase significantly, thereby strengthening market position of insurance companies in the digital era.